Assessment of needs for a European strategy on exposure science: summary report of the first European Exposure Science Strategy Workshop (Building a roadmap 2020-2030) - Bruinen de Bruin, Y. (2019)
The first workshop of the European Chapter of the International Society of Exposure Science (ISES Europe) took place on June 19-20, 2018 in Dortmund, Germany, hosted by the German Federal Institute for Occupational Safety and Health (BAuA). The main objectives of this workshop were: (1) to design the backbone of The European Exposure Science Strategy with a roadmap 2020-2030; (2) to create working groups with their own goals and agenda in alignment with the overall strategy; (3) to identify actions for further research and policy needs in Europe; and (4) to attract ISES Europe members committed to contributing to build the strategy and to increase the visibility of exposure science in Europe. The workshop was structured around six thematic areas that were identified on the basis of a stakeholder survey on needs for exposure science in Europe. These thematic areas were: 1. Data repositories and analytics, 2. Regulatory exposure assessment, 3. Exposure data production and monitoring, 4. Building partnerships and collaboration, 5. Exposure assessment methods and tools, 6. Exposure science education and communication. On the first day, the focus was on assessing the needs, gaps and opportunities for exposure science in Europe, and on the second day, the focus was on identifying building blocks for fulfilling the identified needs. Both days started with keynote lectures and continued with thematic parallel working group sessions along the defined thematic areas. About 120 experts working at nine stakeholder groups participated in the workshop comprising European Commission Services, European Agencies, European Member States’ national authorities, industry, academia, consultants and insurance companies. During the breakout sessions, interactive discussions took place where exposure science practitioners discussed strategic activities and domains relevant for defining a strategy for exposure science to better serving human health and wellbeing, environmental safety needs, inform exposure policy domains, and help product developers and sustainability managers to achieve their goals towards a sustainable development in Europe. The workshop defined building blocks and actions, comprising e.g. the creation of working groups, and initiation of projects responding to the identified needs, concerning exposure science and relevant policies, and the level of coordination needed between the various stakeholders involved in the exposure science-policy interface. It was concluded that the following building blocks and actions are needed as a foundation of a European Exposure Science Strategy being: 1. To establish a common portal on exposure science, 2. To build a European exposure science network and partnerships, 3. To develop a common framework across policies and regulations making use of exposure science by focussing on the alignment of principles and efficiency enhancement, 4. To establish an integrated exposure assessment framework of methods and tools, and 5. To develop an education and training scheme. The present report summarises the workshop’s outcome and represents a first step towards the development of a European Exposure Science Strategy with a roadmap 2020-2030. The report is structured in a way that it first briefly introduces exposure science and its role for the European community (Chapter 1), followed by an overview of the first ISES Europe workshop organization (Chapter 2), the workshop outcome (Chapter 3), and a related brief discussion and some conclusions (Chapter 0). In the appendix, we provide the workshop agenda (Appendix A), a list of participants’ affiliations (Appendix B), names of session chairs, co-chairs, rapporteurs and moderators (Appendix C), the results of the SWOT analyses of the thematic breakout sessions (Appendix D), and a list of posters presented during the workshop (Appendix E).